Detection of methane depletion associated with stratospheric intrusion by atmospheric infrared sounder (AIRS). Issue 10 (31st May 2013) - Xiong, Xiaozhen; Barnet, Chris; Maddy, Eric; Wofsy, S.C.; Chen, Liangfu; Karion, Anna; Sweeney, Colm
<x xml:space="preserve">Abstract</x> [1] Atmospheric methane (CH4) concentration in the mid‐to‐upper troposphere has been retrieved using atmospheric infrared sounder (AIRS) data on NASA EOS/AQUA. By selecting the AIRS strong CH4 absorption channels near 1306 cm−1, severe CH4 depletion was mapped during a stratospheric intrusion event on 27 March 2010. The areas with depleted CH4 mixing ratio are collocated with enhanced ozone (O3) and low tropopause height. Aircraft measurements observed the depleted CH4 and enhanced O3 down to 550 hPa. An estimate of the depleted CH4 amount which resulted from stratospheric intrusion is −54 to −67 Tg yr−1. This study suggests that the AIRS and/or other thermal infrared sounders can provide an observation of CH4 variation associated with stratospheric intrusion, a key unknown in CH4 budget, and this data set will be also useful for studying the stratosphere‐troposphere exchange (STE).